2017
DOI: 10.1002/hed.24827
|View full text |Cite
|
Sign up to set email alerts
|

Salvage surgery for oropharyngeal squamous cell carcinomas: A retrospective study from 2005 to 2013

Abstract: According to the high morbimortality, it is important to carefully select the right patients for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…While it is difficult to compare data across trials in the absence of well accepted guidelines, reported rates of complications following SS for all head and neck subsites ranged from 23% to 67% [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In the absence of uniformity in the reporting of complications, comparison is challenging.…”
Section: Awareness Of Complications In Salvage Surgerymentioning
confidence: 99%
See 4 more Smart Citations
“…While it is difficult to compare data across trials in the absence of well accepted guidelines, reported rates of complications following SS for all head and neck subsites ranged from 23% to 67% [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In the absence of uniformity in the reporting of complications, comparison is challenging.…”
Section: Awareness Of Complications In Salvage Surgerymentioning
confidence: 99%
“…Many studies have identified advanced primary tumor and nodal stage, short disease-free interval (DFI), nonlaryngeal cancer site, and previous RT as oncologic risk factors for poor outcome after SS [ 9 , 17 , 23 , 24 , 25 , 26 ].…”
Section: Oncological Outcomesmentioning
confidence: 99%
See 3 more Smart Citations